Reading Comprehension and Declarative Memory of Psychology Freshmen in Two Campuses of the Universidad Cooperativa de Colombia - Salamanca Velandia, Sandra Rocío; Acevedo Villalobos, Eliana Patricia (Rastros Rostros, 2012)
This paper is given rise from the ongoing research “Reading Comprehension and Declarative Memory in Freshmen of the Faculty of Psychology of the Universidad Cooperativa de Colombia, in the Bucaramanga and Barrancabermeja Campuses”, held from 2010 at the Universidad Cooperativa de Colombia in the two mentioned campuses, and belongs to the research groups “Community Psychology Family and Society” (Bucaramanga campus) and “Psicoba” (Barrancabermeja campus). Given the low levels of reading comprehension associated with semantic memory and its relationship to academic difficulties in the freshmen of such campuses, the final outcome of the research is oriented towards the proposal of pedagogical and building strategies for higher education institutions that strengthen rote skills and reading comprehension to be adopted by institutions of intermediate education.
Keywords: reading comprehension; episodic memory; explicit or declarative memory; human memory; semantic memory